Soft skills in chemistry courses: where, when, and how to assess them? - Sá, Jacinto; Sá, Jacinto (IJRDO- Journal of Educational Research, 2017)
A recent evaluation of chemistry degrees at Uppsala University, Sweden indicatedthat soft skills are not routinely assessed even if the report advocates that they aretaught as an integrant part of the courses syllabus. This opinion article looks into caseexamples, strategies, and methodologies to assess soft skills as an integrant part ofcourse assessment. Purposively, assessment strategies in courses dedicated to softskills teaching and training were avoided.